Interdisciplinary Management of Gingivitis Artefacta Major: A Case Series - Naina Pattnaik; Anurag Satpathy; Rinkee Mohanty; Rashmita Nayak; Surjeet Sahoo (Case Reports in Dentistry)
Cases described here discuss interdisciplinary (periodontal and behavioral) approach in the management of rare and difficult to diagnose self-inflicted injuries of gingiva such as gingivitis artefacta major. Self-inflicted injuries to the gingiva are rare and their management by periodontal therapy alone is inadequate. Proper management of this condition requires early detection and effective psychological treatment through behavioral therapy in addition to the treatment of dental lesion. Three male patients in their twenties presented with traumatic injuries of gingiva with history of self-injury and underlying emotional disturbances. Following basic periodontal intervention, their self-inflicting behavior was confirmed on psychiatric consultation. All of them underwent cognitive behavior therapy and were able to successfully curb their self-inflicting behavior prior to any definitive dental procedures. These cases illustrate the essentiality of behavioral intervention in addition to periodontal procedures in the management of such lesions.